Repeatability and reproducibility of cerebral 23Na imaging in healthy subjects - Meyer, Melissa; Haneder, Stefan; Konstandin, Simon; Budjan, Johannes; Morelli, John N.; Schad, Lothar R.; Kerl, Hans Ulrich; Schönberg, Stefan; Kabbasch, Christoph (BMC medical imaging, 2019)
Initial reports of 23Na magnetic resonance imaging (MRI) date back to the 1970s. However, methodological challenges of the technique hampered its widespread adoption for many years. Recent technical developments have overcome some of these limitations and have led to more optimal conditions for 23Na-MR imaging. In order to serve as a reliable tool for the assessment of clinical stroke or brain tumor patients, we investigated the repeatability and reproducibility of cerebral sodium (23Na) imaging in healthy subjects.
Gesehen am 26.08.2019
Im Titel ist „23“ hochgestellt